Respuesta :

Answer:

Here, the given expression is,

  ( By the cross multiplication ),

Since, an extraneous solution is a solution, which is emerged by solving the equation but it does not satisfying the equation,

But for x = -3, the equation  follows,

⇒ x = -3 is the non-extraneous,

⇒ The given equation has only one solution x = -3 which is non-extraneous.

Step-by-step explanation:

Answer:

x = -3 is not extraneous solution.

Step-by-step explanation:

[tex]\frac{6}{x-3} =\frac{3}{x}\\Cross\,\, Multiply\\6x =3(x-3)\\6x = 3x-9\\6x-3x=-9\\3x= -9\\x=-9/3\\x=-3[/tex]

An extraneous solution is the solution that is obtained by solving the question given but does not satisfy the original equation.

In our case x = -3

Putting value back to the original equation

[tex]\frac{6}{x-3} =\frac{3}{x}\\\frac{6}{-3-3} =\frac{3}{-3}\\\frac{6}{-6} =-1\\-1=-1[/tex]

Since our original equation is satisfied so,

x = -3 is not extraneous solution.